(untitled) (Eurasian Scientific Herald, 2023)
Several cross-sectional studies have established a connection between vitamin-D deficiency and changes in calcium levels with a higher prevalence of insulin resistance and type 2 diabetes. The present investigation explored a potential association between blood vitamin D and calcium levels in health and type 2 diabetes. The present investigation was a cross-sectional study comprising a total of 40 participants. The study involved the categorization of middle-aged and older individuals into two distinct cohorts based on their health status, namely those diagnosed with type 2 diabetes and those who were deemed healthy. This study employed a simple regression analysis to evaluate serum levels of serum 25(OH)D and calcium levels for measuring function. The findings of this investigation. The potential impact of hypovitaminosis D on glycemic dysregulation in individuals with diabetes is noteworthy, as evidenced by the significant reduction in serum 25(OH)D levels observed in the study results. The restoration of Vitamin D levels has been observed to enhance glycemia and insulin secretion in individuals diagnosed with type 2 diabetes and pre-existing hypovitaminosis D. This finding suggests that Vitamin D may play a important role in the development of type 2 diabetes mellitus. The hypothesis has been reinforced by the existence of vitamin D receptors (VDR) and vitamin D-binding proteins (DBP) in pancreatic tissue, as well as the correlation between specific allelic variations in the VDR and DBP genes and glucose tolerance and insulin secretion. The purported mechanism of vitamin D’s impact on type 2 diabetes involves regulating plasma calcium levels, which in turn regulate insulin synthesis and secretion, and directly affect the function of pancreatic beta cells. However, a statistically insignificant reduction was observed in serum Ca levels among the patients compared to the control group. Moreover, various factors, including physical inactivity, inadequate nutrition practices, and obesity, play a significant role in the onset of type 2 diabetes militate findings of this research suggest that the management of calcium and vitamin-D supplements for six months may not have a significant impact on insulin sensitivity or insulin secretion in individuals who are deficient in vitamin D and belong to multiple ethnic groups